Treatment of three pediatric AML co-expressing NUP98-NSD1, FLT3-ITD, and WT1 - Li Liu; Qi Nie; Zugang Xiao; Xin Chen; Chunhui Yang; Xiaoyan Mao; Na Li; Yan Zhou; Qulian Guo; Xin Tian (BMC, 2024)
Abstract During the treatment of 89 pediatric patients with Acute Myeloid Leukemia (AML) at the Hematology Department of Kunming Medical University's Children's Hospital from 2020 to 2023, three patients were identified to co-express the NUP98-NSD1, FLT3-ITD, and WT1 gene mutations. The bone marrow of these three patients was screened for high-risk genetic mutations using NGS and qPCR at the time of diagnosis. The treatment was administered following the China Children's Leukemia Group (CCLG)-AML-2019 protocol. All three patients exhibited a fusion of the NUP98 exon 12 with the NSD1 exon 6 and co-expressed the FLT3-ITD and WT1 mutations; two of the patients displayed normal karyotypes, while one presented chromosomal abnormalities. During the induction phase of the CCLG-AML-2019 treatment protocol, the DAH (Daunorubicin, Cytarabine, and Homoharringtonine) and IAH (Idarubicin, Cytarabine, and Homoharringtonine) regimens, in conjunction with targeted drug therapy, did not achieve remission. Subsequently, the patients were shifted to the relapsed/refractory chemotherapy regimen C + HAG (Cladribine, Homoharringtonine, Cytarabine, and G-CSF) for two cycles, which also failed to induce remission. One patient underwent Haploidentical Hematopoietic Stem Cell Transplantation (Haplo-HSCT) and achieved complete molecular remission during a 12-month follow-up period. Regrettably, the other two patients, who did not receive transplantation, passed away. The therapeutic conclusion is that pediatric AML patients with the aforementioned co-expression do not respond to chemotherapy. Non-remission transplantation, supplemented with tailor-made pre- and post-transplant strategies, may enhance treatment outcomes.